Evaluation of the effectiveness of agricultural cooperative management in optimizing resources and business sustainability - Elfi Rahmadani; Nurhidayati Nurhidayati; Ridal Asri Wahyudi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study evaluates the effectiveness of agricultural cooperative management in optimizing resources and achieving business sustainability. Using a mixed-methods approach, data were collected through surveys involving 150 agricultural cooperatives across five regions in Indonesia and in-depth interviews with cooperative managers. The findings reveal that cooperatives that effectively optimize financial, human, and natural resources experience up to a 60% increase in turnover and a 25% reduction in operational costs, particularly those that incorporate technology such as IoT for real-time monitoring of soil moisture and climate conditions. Regression analysis indicates a strong positive correlation between strategic planning, technology adoption, and cooperative sustainability, with cooperatives implementing structured planning showing consistent growth over 3–5 years. Despite these benefits, challenges remain, including limited managerial training, restricted access to capital, and insufficient participation in decision-making. This study contributes to the literature by offering empirical evidence of the quantifiable impact of technology and structured resource management on cooperative sustainability, filling the gap in previous research that often overlooked the integration of financial, technological, and managerial strategies. The findings underscore the need for policy interventions, increased training programs, and financial support to facilitate technology adoption, ensuring cooperatives remain competitive in the evolving agricultural landscape.